Psychosocial Factors of Adolescent Survivors of Human Trafficking in East India - Sheeba Shamsudeen; Preeti Gupta; Neha Sayeed; Sanjay Kumar Munda (Indian Journal of Social Psychiatry)
Introduction: Human trafficking is referred to as modern-day slavery and is a human rights violation. India is home to 14 million survivors of trafficking, making it one of the most extensive destination grounds for the trafficking of young girls. Empirical studies on trafficking survivors’ demographic profiles and psychosocial factors are scarce in the Indian context. Aims and Objectives: The study determined the various forms of human trafficking and the sociodemographic profile while assessing the psychosocial factors related to pretrafficking, during trafficking, and posttrafficking phases of adolescent female survivors of human trafficking in East India. Materials and Methods: A cross-sectional descriptive study was conducted with 30 adolescent girls aged from 13 to <18 years rescued from human trafficking using the Trafficking Victim Identification Tool to collect data on psychosocial factors related to human trafficking. Statistical Analysis: The analysis was conducted using SPSS version 25. Descriptive statistics were used to calculate the frequency and percentages to assess the sociodemographic and psychosocial factors of adolescent survivors of human trafficking. Results: The results show that most adolescents had experienced physical abuse before trafficking. Most were trafficked by family members or relatives who promised them economic opportunities. During trafficking, most were locked up against their will, experienced physical and sexual violence at the hands of their trafficker, and had no fixed working hours. Most survivors were rescued within 1–3 months of trafficking and had low suicide ideation. In addition, most survivors were unmarried, had primary education, were Hindi-speaking unemployed, Hindu, and from a rural background. Conclusion: The study shows that the most pressing psychosocial factors among survivors of human trafficking include physical abuse before trafficking, physical and sexual abuse by traffickers, and being trafficked by known persons with a promise of economic opportunity. As trafficking is an unrelenting public and mental health concern that transcends all social classes and demographics, further dialogue is needed on survivors’ long-term consequences as the world wakes up to the reality of this modern form of slavery.